Seasonality of the rainfall regime in the mesoregions of the Pernambuco state, Brazil (Research, Society and Development, 2023)
This research aims to classify the rainfall regimes in the Pernambuco municipalities of Petrolina (Sertão of São Francisco), Araripina (Sertão of Pernambuco), Garanhuns (Agreste), Rio Formoso (Zona da Mata) and Abreu e Lima (Metropolitan region of Recife) based on the extraction of seasonality from monthly precipitation data. The study is carried out using the seasonality method, with which the seasonality indices (individual and general) and the replicability index (RI) are calculated, and in the trend analysis using the Mann-Kendall and Sen’s slope methods. The data analyzed were made available by the Agência Pernambucana de Águas e Clima – APAC, and correspond to monthly precipitation records captured between 1995 and 2020 at meteorological stations located in each municipality. Results of the Mann-Kendall and Sen’s slope tests indicated that there was no statistically significant trend in the annual seasonality of rainfall regimes for any of the rainfall stations investigated. According to the general seasonality index, the average rainfall regimes in the municipalities of Garanhuns (Agreste), Rio Formoso (Zona da Mata) and Abreu e Lima (Metropolitan region of Recife) for the analyzed period were classified as rather seasonal with a short dry season, while in the municipalities of Araripina (Sertão of Pernambuco) and Petrolina (Sertão of São Francisco), they were classified as markedly seasonal with a long dry season. Furthermore, all municipalities presented average rainfall regimes with high replicability, the lowest being in Petrolina (with RI = 0.69) and the highest in Rio Formoso (with RI = 0.80).